Visuomotor Integration for Coupled Hand Movements in Healthy Subjects and Patients With Stroke - Iosa, Marco; Ghanbari Ghooshchy, Sheida; Morone, Giovanni; Zoccolotti, Pierluigi; Franceschilli, Simone; Bini, Fabiano; Marinozzi, Franco; Della Croce, Ugo; Paolucci, Stefano; Cereatti, Andrea (Frontiers in Bioengineering and Biotechnology, 2020)
Many studies have investigated the bilateral upper limb coordination during movements under different motor and visual conditions. Bilateral training has also been proposed as an effective rehabilitative protocol for patients with stroke. However, the factors influencing in-phase versus anti-phase coupling have not yet being fully explored. In this study, we used a motion capture device based on two infrared distance sensors to assess whether the up and down oscillation of the less functional hand (the non-dominant one in healthy younger and older subjects and the paretic one in patients with stroke) could be influenced by in-phase or anti-phase coupling of the more functional hand and by visual feedback. Similar patterns were found between single hand movements and in-phase coupled movements, whereas anti-phase coupled movements were less ample, less sinusoidal, but more frequent. These features were particularly evident for patients with stroke who showed a reduced waveform similarity of bilateral movements in all conditions but especially for anti-phase movements under visual control. These results indicate that visuomotor integration in patients with stroke could be less effective than in healthy subjects, probably because of the attentional overload required when moving the two limbs in an alternating fashion.